Combined effects of weight change trajectories and eating behaviors on childhood adiposity status: A birth cohort study. (1st July 2021) - Lin, Qingmin; Jiang, Yanrui; Wang, Guanghai; Sun, Wanqi; Dong, Shumei; Deng, Yujiao; Meng, Min; Zhu, Qi; Mei, Hao; Zhou, Yingchun; Zhang, Jun; Clayton, Peter E.; et al.
Abstract: Previous studies have suggested that infant rapid weight change can be associated with an increased weight later in life. However, the weight change trajectory in early life over time and which childhood lifestyle behaviors may modify the risk of rapid weight change have not been characterized. Using our ongoing birth cohort study, we have addressed these issues. Nine follow-up time points (birth, 3, 6, 9, 12, 18, 24, 36, and 48 months) were used to calculate the change between two adjacent weight-for-age z-scores (WAZ-change), and then WAZ-change trajectories were defined via group-based trajectory modeling. The solitary, independent and combined effects of WAZ-change trajectories and each lifestyle factor (eating behaviors, physical activity, media exposure time and total sleep duration) on childhood adiposity measures at age 4 years were determined using multivariate regression analysis. Overall, 84 (38%) children had a steady growth trajectory from birth to 4 years, while the other 137 (62%) children had an early infancy rapid growth trajectory, particularly in the first three months. Compared to children with steady growth, children with early infancy rapid growth had a significantly higher body mass index, waist circumference, and subcutaneous fat. Moreover, weight change trajectory and three eating behaviors (i.e. food responsiveness, satiety responsiveness and food fussiness), not only had independent effects, but also combined (synergistic) effects on the majority of adiposity measures. Our results extend the current literature and provide a potentially valuable model to aid clinicians and health professionals in designing early-life interventions targeting specific populations, specific ages and specific lifestyle behaviors to prevent childhood overweight/obesity.